1993
DOI: 10.1353/sls.1993.0016
|View full text |Cite
|
Sign up to set email alerts
|

Location, Handshape & Movement: Young Children’s Acquisition of the Formational Aspects of American Sign Language

Abstract: The acquisition of the formational aspects of American Sign Language signs was examined in nine young children of deaf parents. Videotape records of early sign language development were made during monthly home visits. The study focused on the acquisition of the three principal formational components of any ASL sign: location, movement, and handshape. Beginning with the children’s initial sign productions, the location aspect was produced correctly in most instances. The movement aspect was produced significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 17 publications
4
45
0
3
Order By: Relevance
“…Unmarked handshapes are easier to articulate and to distinguish from other handshapes, while marked handshapes are harder to produce and to perceive (Conlin, Mirus, Mauk, & Meier, 2000;Siedlecki & Bonvillian, 1993). Young children often misarticulate signs and replace marked handshapes with unmarked ones, but in doing so retain some of the visual similarity between the target and the child handshape (Marentette & Mayberry, 2000;Morgan et al, 2007).…”
Section: Acquisition Of Sign Language Phonologymentioning
confidence: 99%
“…Unmarked handshapes are easier to articulate and to distinguish from other handshapes, while marked handshapes are harder to produce and to perceive (Conlin, Mirus, Mauk, & Meier, 2000;Siedlecki & Bonvillian, 1993). Young children often misarticulate signs and replace marked handshapes with unmarked ones, but in doing so retain some of the visual similarity between the target and the child handshape (Marentette & Mayberry, 2000;Morgan et al, 2007).…”
Section: Acquisition Of Sign Language Phonologymentioning
confidence: 99%
“…Investigation of the mechanisms of sign phonology have often focused separately on sign handshape (Andin, Rönnberg, & Rudner, 2014;Andin et al, 2013;Grosvald et al, 2012;Wilson & Emmorey, 1997) and sign location (Colin, Zuinen, Bayard, & Leybaert, 2013;MacSweeney, Waters, et al, 2008). Studies that have compared these two phonological parameters identified differences in comprehension and production psycholinguistically (e.g., Orfanidou, Adam, McQueen, & Morgan, 2009;Carreiras, Gutiérrez-Sigut, Baquero, & Corina, 2008;Dye & Shih, 2006;Emmorey, McCullough, & Brentari, 2003), developmentally (e.g., Morgan, Barrett-Jones, & Stoneham, 2007;Karnopp, 2002;Siedlecki & Bonvillian, 1993), and neuropsychologically (Corina, 2000). In particular, the neural signature of handshape and location-based primes has been found to differ between signs and nonsigns and further interact with the semantic properties of signs Gutiérrez, Müller, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on BSL and American Sign Language (ASL) (e.g., Dye & Shih, 2006;Emmorey & Corina, 1990;, including developmental (e.g., Karnopp, 2002;Meier, 2000;Morgan, 2006;Siedlecki & Bonvillian, 1993) as well as neuropsychological (Corina, 2000) studies, has found differences between parameters in sign comprehension and production. But to our knowledge, there are no previous data on online misperception errors in signed languages.…”
mentioning
confidence: 99%